2021
DOI: 10.1002/anie.202016734
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Analysis of Isomeric Unsaturated Lipids through Online Photochemical Derivatization of Carbon–Carbon Double Bonds**

Abstract: Unraveling the complexity of the lipidome requires the development of novel approaches for the structural characterization of lipid species with isomer-level discrimination. Herein, we introduce an online photochemical approach for lipid isomer identification through selective derivatization of double bonds by reaction with singlet oxygen. Lipid hydroperoxide products are generated promptly after laser irradiation. Fragmentation of these species in a mass spectrometer produces diagnostic fragments revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 41 publications
0
58
0
1
Order By: Relevance
“…After only 10 min of accelerated oxidation, the unsaturated lipid isomers in nude lung cancer tissue and human thyroid cancer tissues were successfully imaged by AFADESI. In 2021, for lipid isomer identification, Unsihuay et al reported an online photochemical derivatization approach, i.e., 1 O 2 reacted with lipids to form lipid hydroperoxides (LOOHs), which was then followed by collision-induced dissociation (CID) to obtain diagnostic peaks (Figure 6H) [106]. The Paternò-Büchi (PB) reaction is another commonly used method for identifying the location of C=C double bonds in unsaturated lipids and simplified PB reaction conditions were introduced by spraying the reagent solution on the tissue surface with only 10 min preprocessing [107].…”
Section: Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…After only 10 min of accelerated oxidation, the unsaturated lipid isomers in nude lung cancer tissue and human thyroid cancer tissues were successfully imaged by AFADESI. In 2021, for lipid isomer identification, Unsihuay et al reported an online photochemical derivatization approach, i.e., 1 O 2 reacted with lipids to form lipid hydroperoxides (LOOHs), which was then followed by collision-induced dissociation (CID) to obtain diagnostic peaks (Figure 6H) [106]. The Paternò-Büchi (PB) reaction is another commonly used method for identifying the location of C=C double bonds in unsaturated lipids and simplified PB reaction conditions were introduced by spraying the reagent solution on the tissue surface with only 10 min preprocessing [107].…”
Section: Lipidsmentioning
confidence: 99%
“…(H) Mechanism experiment setup of the online single oxygen reaction with lipids. Reprinted with permission from the authors of [106]. Copyright (2021) Wiley-VCH GmbH.…”
Section: Lipidsmentioning
confidence: 99%
“…In this workflow, the onset of the electro-epoxidation of the C=C bond could be controlled by tuning the voltage, and the diagnostic ions derived from the fragmentation of electro-epoxidized products by MS/MS were used to indicate the C=C positions. To circumvent the challenge in spatially resolving positional isomers in lipidomic analyses, the method for the online selective photochemical derivatization of the C=C bond by singlet oxygen ( 1 O 2 ) was proposed [2]. The mechanism of C=C bond oxidation by 1 O 2 (Figure 5B) can be briefly descripted as follows.…”
Section: Other Strategiesmentioning
confidence: 99%
“…Infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI), as a hybrid soft ionization source based on IR-laser desorption followed by electrospray post-ionization, has been combined with on-tissue m-CPBA epoxidation for the in situ detection of FAs C=C positional isomers in rat liver and human bladder cancer tissue [65]. Furthermore, when coupling the 1 O 2 reaction with nano-DESI-MS, several isomeric lipids from mouse muscle and uterine tissues were directly detected [2]. Recently, an online coupling of the PB reaction and radical-direct fragmentation with in-capillary extraction nanoelectrospray ionization mass spectrometry (ICE-nanoESI-MS) [70] was developed in order to determine C=C locations and stereospecific numbering positions of potential lipid biomarkers for human colorectal cancer under an ambient condition; the results indicated that lysophospholipids could act as potential biomarkers related to the pathogenesis of human colorectal cancer.…”
Section: Direct Characterization Of Unsaturated Lipid Isomers In Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation